“PENGARUH KUALITAS PRODUK, PROMOSI DAN SALURAN DISTRIBUSI TERHADAP LOYALITAS MEREK DIUKUR MELALUI KEPUASAN PELANGGAN “ (Studi Kasus Pada Yamaha Mio Semarang Club) - Hendy Marta Andryanto; Saryadi Saryadi; Widayanto Widayanto (Universitas Diponegoro, 2013)
Brand loyalty became measurement of how much customer possibility will move to other brand. It was the one brand equity element related to profit in the future. Brand loyalty assured customer won't change to competitor's brand, although that brand give cheaper price or better quality. Competition within transportation especially motorcycle, compelled producer created various brand and models to attract customer. Satisfaction and loyalty effort to customer always followed by evaluation to satisfaction level and loyalty reached by costumer. It was needed company management in order to determine marketing strategy which will used in the future properly. This research aimed to found how much influence of product quality, promotion and distribution system to brand distribution measured through customer satisfaction. Population from this research was motorcycle user of Yamaha Mio who joint within Yamaha Mio Semarang Club (YMSC) about 80 persons. This study include within census research, according to Arikunto Suharsini (1996:115) whereas including all of population members as research subject. Measurement scale used scale Likert. Within data analysis used simple linear regression test, double regression test and path analysis by SPSS 16.0 program.